Ernst von Salomon, the Rural People’s Movement [Landvolkbewegung] and the new rules of German things - Kuropka, Joachim (Acta Universitatis Lodziensis. Folia Germanica, 2015)
Based on two of Ernst von Salomon’s literary documents on the Rural People’s Movement [Landvolkbewegung] (1928–1932), this paper will trace the thinking of national revolutionary intellectuals and charismatic Landvolk leaders. Their clear rejection of National Socialism is just as evident as their retreat into a specific form of inner emigration.